Reconstruction of the ancient Jugra dialect - Rahim Aman,; Shahidi A.H.,; Rusydiah A. Salam,; Fatin Hakimah M. Fadzil,; Suhailah Ruslan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study emphasis the reconstruction of vowels, and diphthongs in ancient Jugra dialect (DJP) that exist in Selangor. This study uses a comparative qualitative method to gather data through check and speak method. The data gathering techniques were directed and non-directed interview, as well as recording and picture showing. Reconstruction process of the vowels, and diphthongs was done by employing internal reconstruction. Reconstruction criteria was carried out to determine the cognate words, find the correspondence of phonemes, discover recurrence of phonemes and phoneme ancient gain. The Jugra variants (VJ) in Selangor are variant in Sungai Buaya (SB), Pulau Nyatoh (PN) and Kelanang (KLNG). This study proofs that reconstructed DJP has 6 vowel phonemes which are *i, *e, *a, *ə, *u and *o, two diphtongs, which are *-aj and *-aw. The existence of these ancient phonemes that is made of phonemes vowel, and diphthong took place systematically and can be predicted. The innovation on the five vowel phonemes, for instance, DJP *i, *e, *a, *u *o, took place due to resettlements rural development. Meanwhile, diphthongs in DJP show the existense of linear reconstruction from MP which is *-aj and *-aw. The significance of this study is its contribution towards reconstruction of Ancient Malay Language (AML).